Tram to Pedestrian Collisions—Priorities and Potentials - Lackner, Christian; Heinzl, Philipp; Rizzi, Maria C.; Leo, Christoph; Schachner, Martin; Pokorny, Petr; Klager, Peter; Buetzer, David; Elvik, Rune; Linder, Astrid; Klug, Corina (Frontiers in Future Transportation, 2022)
To improve mobility in cities in line with environmental goals, in urban traffic, trams represent an increasingly important means of transport. Due to the close interaction with other road users, this makes collisions with trams fairly frequent. This study has investigated accidents between trams and vulnerable road users (VRUs) resulting in personal injury, aimed at identifying priorities for simulating collisions between trams and pedestrians to assess passive safety measures. Tram accident data collection established throughout Europe from multiple sources and with varying degree of details, have been combined and analysed. These analyses comprise risk assessments per km-driven and general tram accident partner and site type evaluations, with more detailed analyses on accident site distance to the closest tram stop and injured body regions, respectively. In total, 7535 tram-pedestrian accident resulting in 8802 pedestrian injuries, collected in the year 2000-2021, was analysed. Accident risk ranges from 0,934 accidents per number of tram (million) km-driven, for slight injuries to 0,063 for fatal injuries. Pedestrians represent a large proportion of tram accident collision partners, especially for severe and fatal accidents. In accidents between trams and pedestrians, 3% of reported injuries are fatal, 23% severe and 74% minor. Generally, low-speed accidents close to tram stops often leading to minor injuries were observed to be of significant importance (<20m to the GPS location of a stop). Analysis of accidents was done bases on gender of the pedestrian showing overall similar involvements in accident with slight difference for various age groups and sites. Regardless of injury severity, the most frequently injured body region in accidents involving a tram is the head. Likewise, injuries sustained to the thorax, especially for higher injury severities are of high relevance, followed by injuries to the lower extremities. Based on this study, recommendations for developing reasonable tram-pedestrian accident scenarios for virtual testing can be derived for further optimisation of pedestrian safety of trams.